The triterpenoid saponin content difference is associated with the two type oxidosqualene cyclase gene copy numbers of Pulsatilla chinensis and Pulsatilla cernua - Liu, Xianju; Xu, Yudi; Di, Jipeng; Liu, An; Jiang, Jinzhu (Frontiers in Plant Science, 2023)
Pulsatilla chinensis is an important medicinal herb, its dried radix is used to treat the inflammation since ancient China. Triterpene saponins are proved to be the main active compounds of Pulsatilla genus. The triterpenoid saponin contents vary widely in different Pulsatilla species. But no enzyme involved in the triterpenoid saponin biosynthetic pathway was identified in Pulsitilla genus. This seriously limits the explanation of the triterpene content difference of Pulsatilla species. In this article, we obtained two OSC genes from P. chinensis and P. cernua by touchdown PCR and anchored PCR. These two OSCs converted 2,3-oxidosqualene into different triterpenoids. The OSC from P. cernua is a monofunctional enzyme for β-amyrin synthesis, and the OSC from P. chinensis is a multifunctional enzyme for lupeol and β-amyrin synthesis, and the lupeol is the main product. Then we identified the 260th amino acid residue was the key site for the product difference by gene fusion and site-directed mutant technology. When the 260th amino acid residue was trptophan (W260) and phenylalanine (F260), the main catalysate was β-amyrin and lupeol, respectively. Then we found that the expression of these two genes was strongly correlated with the lupeol-type and β-amyrin-type triterpenoid contents in P. cernua and P. chinensis. Finally, we found the gene copy number difference of these two genotypes leaded to the triterpenoid diversity in Pulsatilla genus. This study provides useful information for the molecular breeding and quality improvement of P. chinensis and a molecular marker to identify the species of Pulsatilla genus.